2001
DOI: 10.1101/gad.940201
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 lysine 4 methylation is mediated by Set1 and required for cell growth and rDNA silencing in Saccharomyces cerevisiae

Abstract: Histone methylation is known to be associated with both transcriptionally active and repressive chromatin states. Recent studies have identified SET domain-containing proteins such as SUV39H1 and Clr4 as mediators of H3 lysine 9 (Lys9) methylation and heterochromatin formation. Interestingly, H3 Lys9 methylation is not observed from bulk histones isolated from asynchronous populations of Saccharomyces cerevisiae or Tetrahymena thermophila. In contrast, H3 lysine 4 (Lys4) methylation is a predominant modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
461
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(486 citation statements)
references
References 59 publications
21
461
3
1
Order By: Relevance
“…Histone H3 from yeast and Tetrahymena are strongly methylated at lysine 4 ('ON' mark), but not at lysine 9 ('OFF' mark). The opposite was observed for H3 in chicken and humans, where lysine 9 was strongly methylated, but not lysine 4 in H3 (Briggs et al, 2001).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Histone H3 from yeast and Tetrahymena are strongly methylated at lysine 4 ('ON' mark), but not at lysine 9 ('OFF' mark). The opposite was observed for H3 in chicken and humans, where lysine 9 was strongly methylated, but not lysine 4 in H3 (Briggs et al, 2001).…”
mentioning
confidence: 76%
“…For example, using chromatin immunoprecipitation (ChIP) assays and site-specific methylation antibodies, elegant studies have shown that lysine 4 methylation vs lysine 9 methylation in histone H3 can mark relatively large chromosomal domains (about 25 -50 kb) with 'active' vs 'inactive' signatures often interrupted by sharp transitions or boundaries that are poorly understood (reviewed in Jenuwein and Allis, 2001;Zhang and Reinberg, 2001;Felsenfeld and Groudine, 2003). Moreover, as depicted in Figure 1B, it appears that the repressive lysine 9 methylation mark in histone H3 is a dominant histone mark in mammalian histones ('OFF'), whereas in lower eukaryotes methylation of lysine 4 in H3 ('ON') dominates (Briggs et al, 2001). This suggests that epigenetic mechanisms exist that lead to a silencing default or ground state in higher organisms.…”
mentioning
confidence: 99%
“…Thus, overexpressed p52 and Hut-78 induce MMP9 expression by tethering a H3K4 HMT complex. Whereas one multi-subunit complex (referred to as COMPASS and Set1 complex) that includes the Drosophila trithorax-related protein Set1 has been shown to trigger the mono-, di-and trimethylation of histone H3K4 in yeast (Briggs et al, 2001;Miller et al, 2001;Nagy et al, 2002;Noma and Grewal, 2002), multiple complexes harbouring robust H3K4 HMT activities have been isolated in mammalian cells and all of them contained one or two SET domain-containing homologues of yeast Set1 (Hughes et al, 2004;Glaser et al, 2006). As those distinct Set-1-like human H3K4 HMT complexes also share common subunits such as ASH2L, RBBP5 and WDR5, we determined whether those proteins interact with p52 by coimmunoprecipitation experiments.…”
Section: Rhd Nls Grr Ankyrin P65mentioning
confidence: 99%
“…Some species might display special histone modification patterns [2] and modification sites (http://research.nhgri.nih.gov/histones/index.shtml) that were not observed in other species [2]. The same modification might function differently in unrelated species [1,2,11,14,16]. Previous studies also showed that some site-specific histone modification differences between animals and plants exist at a genome-wide level [11].…”
Section: Discussionmentioning
confidence: 99%
“…In different organisms, the site [9], sequence [5,10], and level of modification [2,11] may be different in some cases, while conserved in others. Although there is vast information available about the functional role of specific histone modifications [12][13][14], the potential role of histone modification in regulation of development has remained elusive. In this study, we report the characterization of five antibodies that specifically target four modified histone sites and the initial application of those antibodies to determine the levels of those four specific histone modifications in different species as well as in different organs of the selected species.…”
Section: Introductionmentioning
confidence: 99%